2008
DOI: 10.1093/jac/dkn154
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inhibitory effect of voriconazole on the fungicidal activity of amphotericin B against Candida albicans in an in vitro kinetic model

Abstract: Voriconazole inhibited the fungicidal effect of sequentially administered amphotericin B in a concentration- and time-dependent manner; the clinical significance of this needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…Moreover, it was shown that, when the concentration of voriconazole had fallen below the MIC or when voriconazole was washed away, amphotericin B regained its fungicidal effect (13). In the strains of C. albicans resistant to voriconazole and those of C. glabrata and C. krusei with various susceptibilities to voriconazole investigated in the present study, exposure to voriconazole followed by amphotericin B resulted in reduced activity of amphotericin B in all but one strain.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…Moreover, it was shown that, when the concentration of voriconazole had fallen below the MIC or when voriconazole was washed away, amphotericin B regained its fungicidal effect (13). In the strains of C. albicans resistant to voriconazole and those of C. glabrata and C. krusei with various susceptibilities to voriconazole investigated in the present study, exposure to voriconazole followed by amphotericin B resulted in reduced activity of amphotericin B in all but one strain.…”
Section: Discussionmentioning
confidence: 46%
“…This finding suggests that the voriconazole inhibitory effect might be sustained in some isolates. The reason for not recovering the fungicidal activity of amphotericin B after voriconazole exposure despite repeated doses of amphotericin B at 48 h and 72 h in any of the strains is difficult to explain but has also been seen in a previous study (13). It seems unlikely that this phenomenon is caused by voriconazole because of the gradually decreasing voriconazole concentration, which at the time of these amphotericin B exposures should be extremely low.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations